Health modernity: a study of women’s knowledge in different domains of health - Rathi, Garima; Kumar, Sumit (International Journal Of Community Medicine And Public Health, 2025)
Background: Scientific understanding and accurate knowledge of etiology, cure, and prevention of diseases and maintenance of health is precisely known as ‘health modernity’. This research piece examined the health modernity of women, focusing on the knowledge of women about different domains of healthcare. Methods: The present study was conducted among women in Meerut city of Uttar Pradesh state in India. This descriptive study was carried out among 67 women of age-group 21-30 years. Data for the study was collected through in-depth face to face interview method with the help of self-structured interview schedule tool. The collected data were analyzed using appropriate statistical techniques and Microsoft Excel 2010. Results: The results of this study showed that while knowledge about nutrition and family planning was relatively good among women, but in other domains of health modernity, maximum numbers of them had average knowledge. It was found that only in two domains (family planning and nutrition) majority of the studied women exhibited health modernity. Conclusions: These findings provide insight into the scientific knowledge of health and its domains in the context of urban women. Thus, this study underscores the need for women to prioritize healthcare initiatives, provide correct health modernity education, and improve the existing healthcare infrastructure to meet the diverse needs of the present era.